A Content Analysis of Peer-Reviewed Journal Articles Over the Last 20 Years: To What Extent Does Contemporary Research Focus on the Effects of Frequent Relocation on the Academic Performance of Military-Connected Students? - Tyler Fowler (Educational Considerations, 2024)
This article is a content analysis of peer-reviewed research publications from the years 2001 to 2022 to find the extent to which frequent relocation may affect the academic performance of military-connected students. There are many articles with a focus on civilian students that experience frequent residential and school mobility. However, to what extent has the extant literature focused on the military-connected student that also experiences frequent residential and school mobility? This article pays special attention to the current literature surrounding elementary-aged military-connected students. This article also examines areas of future research surrounding this group of students.
Keywords: military-connected students; elementary-aged students; content analysis